Association between the β-blocker use and patients with sepsis: a cohort study - Yang, Qilin; Kong, Tianyu; Bao, Ziping; Yang, Shanshan; Chen, Xiaohua; Zheng, Jiezhao; Xiong, Xuming; Wen, Deliang; Zhang, Zhenhui (Frontiers in Medicine, 2023)
Objective This study aimed to assess whether β-blockers are associated with mortality in patients with sepsis. Method: We conducted a retrospective cohort study of patients with sepsis using the Medical Information Market for Intensive Care (MIMIC)-IV and the emergency intensive care unit (eICU) databases. The primary outcome was the in-hospital mortality rate. The propensity score matching (PSM) method was adopted to reduce confounder bias. Subgroup and sensitivity analyses were performed to test the stability of the conclusions. Results:We included a total of 61,751 patients with sepsis, with an overall in-hospital mortality rate of 15.3% in MIMIC-IV and 13.6% in eICU. The inverse probability-weighting model showed that in-hospital mortality was significantly lower in the β-blockers group than in the non-β-blockers group [HR=0.71, 95% CI: 0.66-0.75, p<0.001 in MIMIC-IV, and HR=0.48, 95% CI: 0.45-0.52, p<0.001 in eICU]. In subgroups grouped according to sex, age, heart rate, APSIII, septic shock, and admission years, the results did not change. Conclusion: β-blocker use is associated with lower in-hospital mortality in patients with sepsis, further randomized trials are required to confirm this association.